GREEN LOGISTICS (GL) FOR ENVIRONMENTAL SUSTAINABILITY: A REVIEW IN SEARCH OF STRATEGIES FOR THAILAND’S GL MANAGEMENT - Sayam Aroonsrimorakot (2022)
There is an increasing interest among both researchers and environmental management practitioners, in the topics of environmental sustainability, and logistics operations, as well as strategies which combine these two concepts as current logistics operations have many negative impacts on the environment. This article offers a systematic literature review of publications in the area of Green Logistics (GL), the significance of GL, and strategies adopted for the best performance of GL management in various countries for environmental sustainability, between the years 2010 and 2022. The study is presented by organization into the sections of introduction, green logistics and its importance for environmental sustainability, strategies for the development of green logistics in Thailand, and a conclusion. Some of the strategies obtained from the literature search for the development of green logistics in Thailand are management of transportation, storage, packaging, and loading and unloading; development of green warehousing; evaluation of logistics operation systems, publicity, promotion, and training; the use of integrated information technology to increase awareness of green logistics, and reverse logistics; and collaboration of organizational and stakeholder pressure. The article is expected to be beneficial to logistics services providers as well as the general public, in developing and implementing green logistics strategies to achieve a sustainable environment for the overall well-being of mankind on a global scale, socially, economically, and environmentally